2018
DOI: 10.1159/000491555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride Toothpaste Containing Nano-Sized Sodium Hexametaphosphate on Enamel Remineralization: An in situ Study

Abstract: Objective: To evaluate the remineralizing potential of a conventional toothpaste (1,100 ppm F) supplemented with nano-sized sodium hexametaphosphate (HMPnano) in artificial caries lesions in situ. Design: This double-blinded crossed study was performed in 4 phases of 3 days each. Twelve subjects used palatal appliances containing 4 bovine enamel blocks with artificial caries lesions. Volunteers were randomly assigned into the following treatment groups: no F/HMP/HMPnano (Placebo); 1,100 ppm F (1100F); 1100F pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Traditional methods, including regular routine visits to the dentist, brushing with uoridated toothpaste supplemented with Ca and P, management of cariogenic diets and topical application of professional uoride, are highlighted in the literature to reduce the incidence of dental caries [19,29,30,31]. The results of this study demonstrated that treatment with 1100F toothpaste associated with 10%CPP-ACP and 3%TMP led to a signi cant change in enamel demineralization and bio lm compared to the 1100F, 1100F-CPP-ACP and 1100F-TMP treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional methods, including regular routine visits to the dentist, brushing with uoridated toothpaste supplemented with Ca and P, management of cariogenic diets and topical application of professional uoride, are highlighted in the literature to reduce the incidence of dental caries [19,29,30,31]. The results of this study demonstrated that treatment with 1100F toothpaste associated with 10%CPP-ACP and 3%TMP led to a signi cant change in enamel demineralization and bio lm compared to the 1100F, 1100F-CPP-ACP and 1100F-TMP treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Final polishing was carried with felt disks moistened with 1 μm diamond solution (Extec Corp. En eld, CT, USA). Next, the blocks were cleaned with deionized water using ultrasound (Unique USC 1400, Indaiatuba, SP, Brazil), operated at 40 Hz and 135 W for 20 min at room temperature [19].…”
Section: Enamel Block Preparationmentioning
confidence: 99%
“…The pH levels of toothpaste slurries were determined using a pH electrode (2A09E, Analyser, São Paulo, Brazil) calibrated with standard pH levels of 7.0 and 4.0. 16 …”
Section: Methodsmentioning
confidence: 99%
“…A layer of enamel (~ 50 µm) was then removed by microabrasion using a modified microscope base with an attached digital manometer (Pantec, São Paulo, Brazil) and 400 grit self-adhesive sanding disc (13 mm diameter) made of silicon-carbide(Buelher) fixed in crystal polystyrene flasks (J-10, Injeplast, Brazil). 16 The resulting enamel powder retained on the polishing discs was then agitated for 1 h after adding 0.5 mL of 0.5 mol L −1 HCl. For F analysis, a specific electrode 9409BN (Thermo Scientific, Beverly, USA) and microelectrode reference (Analyser, São Paulo, Brazil), coupled to an ion analyzer (Orion 720A+, Thermo Scientific, Beverly, USA), were used.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental toothpastes were produced with the following components: titanium dioxide (Sigma-Aldrich); carboxymethyl cellulose (Sigma-Aldrich); methyl p-hydroxybenzoate sodium (Sigma-Aldrich); saccharin (Vetec); peppermint oil (Synth); glycerol (Sigma-Aldrich); abrasive silica (Tixosil 73); and sodium lauryl sulfate (Sigma-Aldrich), adjusted with deionized water to 100 g. NaF (Merck), was added to the F toothpaste to reach a concentration of 1,100 ppm F. 21,22 . A toothpaste with no added F (Placebo) was prepared using the same formulation as the others, and a commercial paste containing CPP-ACP associated with 900 ppm F-MI Paste Plus was used (MI Paste Plus).…”
Section: Formulation Ph Determination and F Concentration In Experime...mentioning
confidence: 99%